Synthesis, Characterization and Application of 2-Line and 6-Line Ferrihydrite to Pb(II) Removal from Aqueous Solution - N Abdus-Salam; FA M’civer (Journal of Applied Sciences and Environmental Management)
Studies were carried out on the synthesis and characterization of 2-line and 6-line ferrihydrite. The XRD diffraction patterns for 2-line ferrihydrite exhibits two main peaks, a first-order peaks in the region 32.80O and 67.69O 2 with an intensities 100 and 80% respectively. The 6-line ferrihydrite gave a characteristics five essential diffraction pattern with first order peaks in the regions 7.4, 30.0, 31.1, 33.8 and 62.8 O 2 corresponding to 60, 60, 100, 100 and 50% intensities respectively. The XRF results of 2-line ferrihydrite and 6-line ferrihydrite showed Fe as the only major element. The percentage Fe was 95.20% and 93.42% for 2-line and 6-line ferrihydrite respectively. The Point of Zero Charge (pzc) of the 2-line and 6-line ferrihydrite was found to be 7.96 and 6.20 respectively. The 2-line ferrihydrite sorption capacity for Pb(II) was 127mg/g while it was 82mg/g for 6-line ferrihydrite. Adsorption was influenced by pH with maximum adsorption at pH 4 where 87.65% Pb(II) were adsorbed, after which sorption steadily decreased with increasing pH. The experimental results of Pb(II) adsorption were analyzed using Langmuir, Freundlich, and Temkin isotherms. Only Langmuir isotherm fitted the measured sorption data well. The constants obtained from the Langmuir model are 0.017, 1.72 and 0.768 for b, Qm and the regression coefficient R2 respectively; while the 6-line ferrihydrite are 0.02, 1.99 and 0.911 for b, Qm and the regression coefficient R2 respectively.